MY SAY: 'Flopping' for the new year - Abd Razak, Dzulkifli (2008)
Some 40 years ago, at the 1968 Olympics in Mexico City, a new record for the high jump was set — 2.24m or 7ft 4.25in. While the record now stands at 2.39m — held by Charles Austin since the 1996 Atlanta Games — it was no ordinary feat since it did stand the test of time. What was unique about it was the way the record was set by one hitherto unknown Richard Fosbury, who invented the now famous "Fosbury Flop" — a revolutionary style of jumping. But a flop it is not; rather, it took the world of high jumping into another era of sportsmanship and achievement. Long before the flop, high jumpers preferred the "straddle jump" — crossing the bar with the body horizontally facing the ground.